2021
DOI: 10.1172/jci.insight.151078
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial stem cell homeostasis in Meibomian gland development, dysfunction, and dry eye disease

Abstract: Dry eye disease affects over 16 million adults in the U.S. and the majority of cases are due to Meibomian gland dysfunction. Unfortunately, the identity of the stem cells involved in Meibomian gland development and homeostasis are not well-elucidated. Here, we report that loss of Krox20, a zinc-finger transcription factor involved in development of ectoderm-derived tissues, or deletion of KROX20-expressing epithelial cells disrupts Meibomian gland formation and homeostasis, leading to dry eye disease secondary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 38 publications
5
9
0
Order By: Relevance
“…The KROX20 gene and Krox20-lineage cells were shown to be necessary to generate the full, mature meibomian gland extending from the lid margin through the entire length of the meibomian gland structure. 9 This observation is consistent with our previous ARVO 2022 study, which we report in detail within this manuscript, suggesting a cell population at the lid margin consisting of orifice-associated rete ridge epithelial/basement membrane structures (OARREBS) in continuity with and may differentiate into ductal basal epithelium and basement membrane. 10 Furthermore, these rete ridge structures may be activated by the mechanical stimulation of gland probing leading to increased duct wall epithelial cell layers and thickness (in previous studies of meibomian glands using IVCM, rete ridge structures consisting of an epithelial/basement membrane ring surrounding a dermal core (papilla) in proximity to meibomian glands had been initially incorrectly thought to be acinar units.)…”
Section: Introductionsupporting
confidence: 93%
See 1 more Smart Citation
“…The KROX20 gene and Krox20-lineage cells were shown to be necessary to generate the full, mature meibomian gland extending from the lid margin through the entire length of the meibomian gland structure. 9 This observation is consistent with our previous ARVO 2022 study, which we report in detail within this manuscript, suggesting a cell population at the lid margin consisting of orifice-associated rete ridge epithelial/basement membrane structures (OARREBS) in continuity with and may differentiate into ductal basal epithelium and basement membrane. 10 Furthermore, these rete ridge structures may be activated by the mechanical stimulation of gland probing leading to increased duct wall epithelial cell layers and thickness (in previous studies of meibomian glands using IVCM, rete ridge structures consisting of an epithelial/basement membrane ring surrounding a dermal core (papilla) in proximity to meibomian glands had been initially incorrectly thought to be acinar units.)…”
Section: Introductionsupporting
confidence: 93%
“… 12 In our study, confocal microscopy findings revealed lid margin orifice-associated rete ridge structures are in continuity with MG distal duct BM and basal epithelial cell layers and therefore may play a fundamental role in the formation of the MG ductal compartment and would be consistent with Krox20 genetic study. 9 , 14 Furthermore, that MGP stimulated a proliferative epithelial response characterized by accelerated formation of the ductal basement membrane with increased DWECL, DWT, and lumen area at two separate duct foci. Control glands that had not been probed showed no significant change in distal duct microanatomy over a similar follow-up period.…”
Section: Discussionmentioning
confidence: 94%
“…Stem cells involved in the development of meibomian glands have not been well demonstrated thus far, posing an obstacle to meibomian gland regeneration. Recently, a stem/progenitor cell population expressing Krox20, a zinc finger transcription factor, was identified as a crucial driver of the development and homeostasis of the meibomian gland, 162 shedding light on the identification of meibomian gland stem cells and the subsequent construction of meibomian gland substitutes. In addition to regenerating the meibomian glands, engineering tarsal equivalents by directly seeding lipid‐secreting sebocytes onto scaffolds presents another feasible approach 16 .…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…Geraint et al illustrated that it is possible for label-retaining cells to govern the turnover of MGs, and these cells could be identified as two distinct unipotent progenitors that generate ducts and acini independently [ 31 ]. According to the study by Edem et al, KROX20 labels a stem/progenitor cell population that differentiates to produce MGs [ 32 ]. Chen et al found the differences in the components of the extracellular matrix (ECM) surrounding the MG acini, ducts, and the junctions between them [ 26 ].…”
Section: Physiology Of Mgmentioning
confidence: 99%